Exploring the role of rotavirus, adenovirus, and norovirus in gastroenteritis among children in Iraq: an epidemiological and molecular study - Mahmood, Rana Fattah; Frikha, Fakher; Latif, Ismail Ibrahim; Ghonaim, Ahmed H.; Bougacha-Elleuch, Noura (Frontiers in Virology, 2026)
Background and aimAcute gastroenteritis (AGE) is a major cause of morbidity and mortality among children <5 years, with rotavirus A (RVA), adenovirus (AdV), and norovirus (NoV) being key viral agents. Co-infections may contribute to worse outcomes and viral evolution. Data on RVA co-infections and VP6 molecular characteristics in Iraq are limited. This study investigated the epidemiology of the three viruses and characterized RVA VP6 to address this gap.Materials and methodsFrom September 2022 to August 2023, 170 stool samples were collected from children with AGE admitted to AL-Batool Teaching Hospital. All samples  were tested for RVA, AdV, and NoV by RT-PCR. VP6 subgrouping and phylogenetic analyses were performed on RVA-positive samples, and homology modeling with molecular dynamics simulations assessed structural impacts of VP6 amino acid changes.ResultsRVA, AdV, and NoV rates were 45%, 6%, and 3%, respectively. Overall, 86% of samples were positive for one or more viruses, and co-infections were detected in 4.1%, predominantly RVA–AdV. Rural residence and children aged 0–12 months were significantly associated with RVA infection, with seasonal peaks in winter and spring. VP6 subgroup II predominated (84.2%) and was associated with severe diarrhea. All VP6 sequences clustered within the DS-1-like (I2) lineage, sharing >98% identity with regional strains. Key substitutions (I38L, F63L, R117G) increased VP6 monomer stability without affecting trimer assembly.ConclusionAlthough co-infections were infrequent, their clinical relevance and the high viral loads observed underscore the need for ongoing surveillance of enteric viruses in Iraqi children with AGE. This study provides the first molecular and structural characterization of RVA VP6 in Iraq, highlighting the evolutionary stability of the DS-1–like backbone and its importance for genomic surveillance and vaccine development.